Tritiated Water Induces Toxicity in Human Umbilical Vein Vascular Endothelial Cells via IL8. Issue 3 (3rd July 2020) - Yan, Hong-Bin; Liu, Yi-Tong; Li, Zhen-Yan; Wu, Zhuo-Jun; Zhang, Meng; Xue, Pei-Jun; Liu, Yu-Long; Wang, Kong-Zhao; He, Yong-Ming; Tu, Yu; Cui, Feng-Mei; Chen, Qiu
We aimed to determine the toxic effects of tritiated water (HTO) on 12 generations (T1-T12) of human umbilical vein vascular endothelial cells (HUVECs) and elucidate the underlying mechanisms. We evaluated cellular senescence, interleukin (IL) 8 concentrations, and angiogenesis using β-galactosidase staining, enzyme-linked immunosorbent assay, and in vitro assays, respectively. The adhesion properties of contaminated cells and differentially expressed genes were assessed using the xCELLigence RTCA SP system and gene chip analysis, respectively. We found that long-term exposure to low levels of HTO can reduce the adhesion of HUVECs to the cellular matrix as well as their angiogenic capacity, while increasing their permeability, senescence, and adhesion to monocytes. Interleukin 8 activated the p38 and Epidermal Growth Factor Receptor (EGFR) pathways in HTO-treated cells and hence was identified as a key candidate of biomarker. The present study clarified the toxicity of HTO in vascular endothelial cells and identified IL8 as a novel protective target with important theoretical and practical values.